THE INFLUENCE OF LECTURER COMPETENCE ON THE QUALITY OF EDUCATION IN THE MANAGEMENT DEPARTMENT OF UKIP MAKASSAR - Johannes Baptista Halik; Nurlia Nurlia (Program Studi Manajemen Fakultas Ekonomi Universitas Balikpapan, 2024)
One of the problems facing the world of education in Indonesia is the problem of weak learning processes. This research aims to see the influence of lecturer competence on the quality of education in the Management department at the UKIP Makassar campus. This research uses a quantitative approach with SPSS as the data processing application. The sample in this study consisted of 73 students who were students from the 2019 - 2022 class. From the research results it was found that the competence of management lecturers had a positive and significant effect on the quality of education received by students majoring in Management at the UKIP Makassar campus. For this reason, the author suggests that lecturers who teach in the Management department further improve their competence in order to improve the quality of education at UKIP Makassar. Apart from that, the leadership should further increase supervision of lecturers' performance and continuously communicate about the tasks that lecturers must carry out, especially those related to learning. So that all lecturers can be more responsible for the tasks given.